DRY REFORMING OF METHANE FOR SYNGAS PRODUCTION OVER Ni-Co SUPPORTED Al2O3-MgODOPED Zr-Nb CATALYSTS - ABD GHANI, NUR AZEANNI (2019)
DRM is one of the alternatives to produce syngas by utilizing the main greenhouse gases which are CO2and CH4to reduce environmental emissions. However, the use ofNi-basedcatalysts. i.e.Ni/Al2O3 catalyst for DRM reaction brought a drawback impact to the reaction as it contributes to the formation of coke and sintering of catalyst at high temperature which led to low reactants conversion and syngas production. Thus, this research focused on the development studies on the catalyst which has the potential to increase the reactants conversion and syngas production in the DRM reaction. In this work, five catalysts were developed for the production of syngas by synthesizing Ni-Co catalyst with Al2O3,andMgO supports and doped with Zr-Nb promoters.